Viral aetiology of central nervous system infections in adults admitted to a tertiary referral hospital in southern Vietnam over 12 years. - Le Van Tan; Le Hong Thai; Nguyen Hoan Phu; Ho Dang Trung Nghia; Ly Van Chuong; Dinh Xuan Sinh; Nguyen Duy Phong; Nguyen Thi Hoang Mai; Dinh Nguyen Huy Man; Vo Minh Hien; Nguyen Thanh Vinh; Jeremy Day; et al. (Public Library of Science (PLoS), 2014)
Central nervous system (CNS) infections are important diseases in both children and adults worldwide. The spectrum of infections is broad, encompassing bacterial/aseptic meningitis and encephalitis. Viruses are regarded as the most common causes of encephalitis and aseptic meningitis. Better understanding of the viral causes of the diseases is of public health importance, in order to better inform immunization policy, and may influence clinical management.Study was conducted at the Hospital for Tropical Diseases in Ho Chi Minh City, a primary, secondary, and tertiary referral hospital for all southern provinces of Vietnam. Between December 1996 and May 2008, patients with CNS infections of presumed viral origin were enrolled. Laboratory diagnostics consisted of molecular and serological tests targeted at 14 meningitis/encephalitis-associated viruses. Of 291 enrolled patients, fatal outcome and neurological sequelae were recorded in 10% (28/291) and 27% (78/291), respectively. Mortality was especially high (9/19, 47%) amongst those with confirmed herpes simplex encephalitis which is attributed to the limited availability of intravenous acyclovir/valacyclovir. Japanese encephalitis virus, dengue virus, herpes simplex virus, and enteroviruses were the most common viruses detected, responsible for 36 (12%), 19 (6.5%), 19 (6.5%) and 8 (2.7%) respectively, followed by rubella virus (6, 2%), varicella zoster virus (5, 1.7%), mumps virus (2, 0.7%), cytomegalovirus (1, 0.3%), and rabies virus (1, 0.3%).Viral infections of the CNS in adults in Vietnam are associated with high morbidity and mortality. Despite extensive laboratory testing, 68% of the patients remain undiagnosed. Together with our previous reports, the data confirm that Japanese encephalitis virus, dengue virus, herpes simplex virus, and enteroviruses are the leading identified causes of CNS viral infections in Vietnam, suggest that the majority of morbidity/mortality amongst patients with a confirmed/probable diagnosis is preventable by adequate vaccination/treatment, and are therefore of public health significance.